Fostering innovation : how to build an amazing IT team - Laudato, Andrew (Ascent Audio, 2022)
Proven and practical strategies for leading IT teams and departments In Fostering Innovation: How to Build an Amazing IT Team, accomplished technology strategist, executive, and leader Andrew Laudato delivers an eye-opening exploration of how to design, build, staff, and run a high-performing IT department. The book is filled with universally applicable strategies and techniques that can transform any IT team into an all-star cast perfectly aligned with your organization's objectives. Incorporating proven and practical processes throughout the narrative, the book offers useful continuous improvement concepts the reader can apply to their team, company, and professional development. Listeners will also find: foolproof ways to put people before technology; detailed discussions of perennially important topics, like the importance of uptime, how to deploy redundancy, and creating the perfect organization chart; and strategies for managing and motivating the wonderfully unique individuals we refer to as "technologists." The perfect resource for newly minted chief information officers and chief technology officers, Fostering Innovation will also earn a place in the libraries of non-technical professionals who work closely with IT, and business leaders seeking a better understanding of how to lead an IT team